Formulasi Sediaan Gel Variasi Konsentrasi Ekstrak dan Limbah Bunga Mawar Merah (Rosa damascena Mill.) - Diyan Sakti Purwanto; Dewi Weni Sari; Diana Tanafasa (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Red roses (Rosa damascena Mill.) are known to contain active compounds such as flavonoids, tannins, and vitamin C, which have potential antioxidant and anti-inflammatory properties. However, the utilization of rose flower waste after extraction remains limited. This study aims to formulate and evaluate gel preparations based on red rose extract and post-extraction rose flower waste as an innovation in natural-based topical formulations. This research is an experimental laboratory study using a post-test only design. Three concentration variations were formulated for both the extract (F1, F2, F3) and rose flower waste (F4, F5, F6) using HPMC as the gel base. Physical evaluations included organoleptic testing, homogeneity, pH, adhesion, spreadability, and viscosity. Data were analyzed descriptively and statistically using the Kruskal–Wallis test to determine the effect of concentration variation on physical parameters. All formulations showed good organoleptic and homogeneity results. The pH values were within the safe range for skin (4.75–5.92). Adhesion times met the criteria of >1 second, with a tendency to increase alongside higher concentrations of active ingredients. Spreadability fell within the acceptable range (3–5 cm), decreasing as viscosity increased. The viscosity values ranged from 20,150 to 20,182 cps. There was a significant effect of concentration variation on pH (p < 0.05), adhesion in extract-based gels (p = 0.021), and spreadability in waste-based gels (p = 0.024). In conclusion, gel preparations made from red rose extract and its waste can be successfully formulated with good physical stability and meet standard criteria for topical formulations. Rose flower waste has potential as an alternative active ingredient in the development of natural-based gel products.